PERENCANAAN SIMPANG EMPAT BERSINYAL PASAR LEMABANG KOTA PALEMBANG DENGAN PROGRAM SIMULASI VISSIM - Rahman, Abdul (CANTILEVER, 2016)
Lemabang Market is located at a crowded junction in Palembang city, which connect four streets, namely Jl. Yos Sudarso, Jl. Jendral Bambang Utoyo, Jl. RE. Martadinata, and Jl. Ratu Sianum. The intersection has traffic signals, but no traffic signs. The condition of the four approaching roads are narrow. Jl. RE Martadinata and Jl. Yos Sudarso have heavy traffic volume, while Jl. Jendral Bambang Utoyo and Jl. Ratu Sianum have less traffic. This study is aimed to evaluate the performance of the intersection, the existing condition of the traffic, and analyze several alternative traffic arrangements by creating some alternative solutions by means of VISSIM 8. The traffic counting survey was done, as well as inventory survey for road and intersection of Lemabang. The result of simulation model shows that the improvement of median, road geometric and remove the blocking in the middle of junction give better performance in alternative 1 and alternative 2.